Analisis Land Surface Emissivity menggunakan Data NDVI Landsat 8 dan Pengaruhnya terhadap Formasi Land Surface Temperature di Wilayah Kota Kendari - Nurgiantoro, Nurgiantoro; Aris, Armayanti (Jurnal Penginderaan Jauh Indonesia, 2019)
Land surface emissivity (LSE) is an important part of urban environment studies, because these parameters are closely related to the material composition of an urban area, and also main role in analysis of land surface temperature (LST). The remote sensing approach using sensor OLI and TIRS onboard Landsat 8 will make it easier to find out the results. The goal of this study is to analyze the variation of LSE and its effect on LST formation in Kendari region within the last 5 years from 2014 and 2019 based on NDVI thresholds method (NDVITHM). The results show LSE values in the study area an average of ? > 0.96 in the emissivity unit. Whereas the NDVI has an average of 0.64 and 0.74 for 2014 and 2019, respectively. Formation of LST an average of 31.74 °C in 2014, and 23.47 °C in 2019 or approximately 7 °C difference from five years ago.